Avenues to autoimmune arthritis triggered by diverse remote inflammatory challenges. (September 2016) - Chevalier, Nina; Tan, Jian K.; Mason, Linda J.; Robert, Remy; McKenzie, Craig I.; Lim, Florence; Wong, Connie H.; Macia, Laurence; Thorburn, Alison N.; Russ, Brendan E.; Masters, Seth L.; Mackay, Charles R.
Abstract: Environmental factors contribute to development of autoimmune diseases. For instance, human autoimmune arthritis can associate with intestinal inflammation, cigarette smoking, periodontal disease, and various infections. The cellular and, molecular pathways whereby such remote challenges might precipitate arthritis or flares remain unclear. Here, we used a transfer model of self-reactive arthritis-inducing CD4 + cells from KRNtg mice that, upon transfer, induce a very mild form of autoinflammatory arthritis in recipient animals. This model enabled us to identify external factors that greatly aggravated disease. We show that several distinct challenges precipitated full-blown arthritis, including intestinal inflammation through DSS-induced colitis, and bronchial stress through Influenza infection. Both triggers induced strong IL-17 expression primarily in self-reactive CD4 + cells in lymph nodes draining the site of inflammation. Moreover, treatment of mice with IL-1β greatly exacerbated arthritis, while transfer of KRNtg CD4 + cells lacking IL-1R significantly reduced disease and IL-17 expression. Thus, IL-1β enhances the autoaggressive potential of self-reactive CD4 + cells, through increased Th17 differentiation, and this influences inflammatory events in the joints. We propose that diverse challenges that cause remote inflammation (lung infection or colitis, etc.) result in IL-1β-driven Th17 differentiation, and this precipitates arthritis in genetically susceptible individuals. Thus the etiology of autoimmune inflammatory arthritis likely relates to diverse triggers that converge to a common pathway involving IL-1β production and Th17 cell distribution. Graphical abstract: Highlights: Diverse environmental triggers may underlie the etiology of autoimmune arthritis. Intestinal and bronchial inflammation could boost arthritis in susceptible mice. Both challenges triggered IL-1β-mediated IL-17 expression in self-reactive CD4 + . IL-17 + self-reactive CD4 + had an enhanced potential to boost joint inflammation. Inflammation that serves to protect the host can also prime autoreactive CD4 + .